Stolen focus: why you can't pay attention - Hari, Johann (New Delhi Bloomsbury, 2022)
In this book, author tackles the profound dangers facing humanity from information technology and rings the alarm bell for what all of us must do to protect ourselves, our children and our democracies.
Keywords: Distraction (Psychology)